Effect of Alloxan on Some of Biochemistry Parameters in Serum Rats - YASAR, SEMA; OTO, GOKHAN; DEMIR, HALIT; CEBI-ILHAN, AYSEGUL (Asian Journal of Chemistry, 2010)
This study was carried out to investigate whether alloxandiabetic rats could affect biochemical parameters in serum. Twelve Sprague-Dawley albino rats were divided into two experimental groups, i.e., control and alloxan-diabetic rats. A single dose (100 mg/kg) of alloxan was injected intraperitonealy to the treatment rats. Control rats were given only the same amount of physiological saline. Various biochemical constituents of rat were determined after treatment with the alloxan, which caused significant increases in glucose and alanine aminotransferase (ALT) for 1, 3 and 6 h after the treatment, while the level of cholesterol was decreased. Aspartate aminotransferase (AST) level did not change in 1, 3 and 6 h. It is concluded from the experimental of this study that alloxan may cause diabetic in rats.